MENDESAIN SISTEM PENANDA PADA PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) NEGERI 17 SENEN RAYA - Wardani, Winny Gunarti Widya; Sidhartani, Santi; Winarni, Rina Wahyu (PROFICIO, 2024)
The Community Service activity entitled "Implementation of Signage System at the Community Learning Center (PKBM) Negeri 17 Senen Raya" located at Jl. Kramat Sentiong I Rt 006/ Rw 05, Kelurahan Kramat, Kecamatan Senen, Jakarta Pusat, is part of the tri-dharma activities of Higher Education Institutions. PKBM Negeri 17 Senen Raya serves as a learning center for economically disadvantaged individuals or those facing obstacles in attending formal education. It conducts non-formal learning activities to fulfill the educational levels of Elementary School, Junior High School, and Senior High School, through the learning process and examination of diploma modules for Package A (Elementary School), Package B (Junior High School), and Package C (Senior High School). PKBM Senen Raya is under the jurisdiction of PKBM Negeri 17 Tanjung Priok, located in North Jakarta. Based on observations and interviews with PKBM Senen Raya, it was found that one of the challenges faced by the institution is the absence of a signage system that identifies the location at the entrance and the identification of building signs indicating the learning center of PKBM Negeri 17 Senen Raya. This lack of information boards and socialization hinders the community's involvement and access to learning activities. The implementation of this Community Service activity is aligned with the field of Visual Communication Design, involving the design of a signage system for location and building identification where learning activities take place. The presence of these two signage systems is expected to support the dissemination of the education equality program at PKBM Negeri 17 Senen Raya, raise awareness among the local community about the importance of education, encourage anyone interested to participate as volunteer instructors or learners, and simultaneously support the government's education equality program for all segments of society.